Beyond cholesterol: Exploring serum ferritin’s and high-sensitivity C-reactive protein role in cardiovascular risk (Asian Journal of Medical Sciences, 2024)
Background: Iron, a pivotal element in the oxidation of low-density lipoprotein (LDL) cholesterol, exerts influence on inflammatory responses and exhibits a positive association with coronary heart disease. Elevated levels of the inflammatory marker, C-reactive protein (CRP), serve as a predictive risk factor for subsequent cardiac events.Aims and Objectives: This study explores the interplay between cardiovascular disease risk factors and serum ferritin concerning CRP.Materials and Methods: A cohort of 750 subjects (375 males and 375 females) was subjected to analysis. Elevated levels were defined as CRP >3.0 mg/L, serum ferritin >200 ng/mL, total cholesterol >200 mg/dL, and LDL-cholesterol >160 mg/dL. HDL cholesterol levels below 40 mg/dL were categorized as low.Results: Within the low LDL-cholesterol group, no discernible correlation was observed between serum ferritin and high-sensitivity CRP (hsCRP) (odds ratio [OR] of 54.95, 95% confidence interval [CI] = 0.81–3.48, P